A teaching experience in Spain - Di Vita, Alessandro (Formazione & insegnamento, 2019)
Within the 30-hours course of Orientación socioprofesional, 30 students of University of Navarra (Pamplona) enrolled in the five-years degree in Pedagogía y Educación Primaria participated in two educational activities between 4 March and 4 April 2019: one laboratory based on reciprocal teaching and six expressive writing sessions. The educational interventions aimed at dampening the study overload stress in which the students were in and promote their sense of self-efficacy.